Effectiveness of structured, hospital-based, nurse-led atrial fibrillation clinics: a comparison between a real-world population and a clinical trial population. Issue 1 (13th January 2016) - Qvist, Ina; Hendriks, Jeroen M L; Møller, Dorthe S; Albertsen, Andi E; Mogensen, Helle M; Oddershede, Gitte D; Odgaard, Annette; Mortensen, Leif Spange; Johnsen, Søren Paaske; Frost, Lars
Abstract : Objective: A previous randomised trial showed that structured, nurse-led atrial fibrillation (AF) care is superior to conventional AF care, although further research is needed to determine the outcomes of such care in a real-world setting. We compared the outcomes of patients in real-world, nurse-led, structured hospital AF clinics with the outcomes of a randomised trial of the efficacy of a nurse-led AF clinic, with respect to a composite outcome of cardiovascular-related hospitalisation and death. Methods: All patients were referred to the AF nurse specialist by cardiologists. The AF nurse specialist provided patient education, risk-factor control and stimulated empowerment and compliance. During follow-up, treatment was adjusted according to clinical guidelines. Patient education was repeated, and compliance with medical treatment was controlled. The study size was powered as a non-inferiority study. Outcome measures were adjudicated by the same principles in both cohorts. Results: A total of 596 patients from the real world and 356 patients from a clinical trial were included in this study. No significant difference between groups with respect to age, type of AF or CHA2 DS2 VASc score was found. The composite primary end point occurred with an incidence rate of 8.0 (95% CI 6.1 to 10.4) per 100 person-years in the real-world population and 8.3 (95% CI 6.3 to 10.9) per 100 person-years in the clinical trial, with a crude HR of 0.83 (95% CI 0.56 to 1.23). Conclusions: Structured, nurse-led, hospital-based AF care appears to be effective, and patient outcomes in an actual, hospital-based, structured AF care are as least as good as those in trial settings.